Nutrition education and counselling by frontline health and nutrition care workers is associated with improved iron adherence among pregnant women: evidence from the National Family Health Surveys, 2015-21 - Raut, Manoj Kumar; Reddy, J. C.; Warvadekar, Kirti; Babre, Ameet; Varghese, Mini; Jagtap, Shailesh; Islam, M. Mofijul (International Journal Of Community Medicine And Public Health, 2023)
Background: Anaemia is a global public health problem affecting developing and developed countries with major consequences for human health and social and economic development. Methods: This paper attempted to understand the determinants of iron adherence among women of reproductive age during their last pregnancy in India and states/union territories, the iron deficiency being associated with anaemia, using multiple logistic regression analyses of data from the fourth (2015-16) and fifth (2019-21) rounds of the India National Family Health Survey. The individual unit-level data were analysed using Stata 17 software. Results: After adjusting for standard covariates, it was found that those who reported receiving counselling by a frontline health worker and/or antenatal care visits were much more likely to consume at least 90 days of iron-containing supplements. Results shows that for NFHS-4 women who had received counselling from a frontline health and nutrition care worker were 1.489 times (95% CI: 1.429-1.553) to adhere to at least 90 days of iron tablets or syrup after adjusting for potential confounders and for NFHS-5 women who had received counselling from a frontline worker were 1.162 times (95% CI :1.124-1.200) more likely to adhere to IFA supplements or syrup for at least 90 days. Conclusions: Based on insights from these analyses, it appears that counselling seems to be effective in making women aware of the benefits of IFA, thus increasing the likelihood of intake of iron-containing supplements. Counselling seems to be an important predictor of adherence to iron intake in India.